2020
DOI: 10.1007/s12079-020-00558-3
|View full text |Cite
|
Sign up to set email alerts
|

CUDC-907 enhances TRAIL-induced apoptosis through upregulation of DR5 in breast cancer cells

Abstract: CUDC‐907 is a novel dual‐acting inhibitor of phosphoinositide 3‐kinase (PI3K) and histone deacetylase (HDAC). In this study, we aimed to explore the anticancer effects of CUDC‐907 on human breast cancer cells. Our results showed that CUDC‐907 effectively inhibited breast cancer cell proliferation. Flow cytometry analysis revealed that CUDC‐907 induced cell cycle arrest and apoptosis in breast cancer cells. The combined treatment of CUDC‐907 and tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Our results demonstrated the effect of CUDC-907 in inhibiting the PI3K/AKT, HDACs, and enhancing the H3K9Ac levels in NB. Numerous reports in different cancers have shown similar results of the CUDC-907-mediated inhibition of PI3K, HDACs, and related proteins [ 20 , 21 , 32 , 35 , 37 , 38 ]. MYCN is one of the most important prognostic factors for the NB progression [ 46 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our results demonstrated the effect of CUDC-907 in inhibiting the PI3K/AKT, HDACs, and enhancing the H3K9Ac levels in NB. Numerous reports in different cancers have shown similar results of the CUDC-907-mediated inhibition of PI3K, HDACs, and related proteins [ 20 , 21 , 32 , 35 , 37 , 38 ]. MYCN is one of the most important prognostic factors for the NB progression [ 46 ].…”
Section: Discussionmentioning
confidence: 65%
“…In glioblastoma, CUDC-907 induces G1 cell cycle arrest through CDKN1A promoter hyperacetylation-driven transcriptional activation and downregulation of CDK1 [ 36 ], while in lung fibroblast cells, CUDC-907 blocks G1 and S phase [ 37 ]. In breast cancer, CUDC-907 enhances TRAIL-induced apoptosis through the upregulation of cell survival proteins, including XIAP, Bcl-xL, and Bcl-2 [ 38 ]. The oncogenic activation of PI3K/AKT signaling pathway regulates multiple parallel signaling pathways, which are known to be involved in metabolism, proliferation, motility, and autophagy in different cancers [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some chemotherapy agents induce cell cycle arrest by upregulating the expression of inhibitors of cyclins and CDKs. [ 21,22 ] We found that treatment with SBT‐A upregulated the expression of p21 in both the HepG2 and Huh7 cells and increased that of p27 only in the HepG2 cells.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, CUDC-907 enhanced the phosphorylation of p38 MAPK and JNK. JNK inhibition blocked CUDC-907-induced DR5 upregulation (30). Collectively, these findings suggested that CUDC-907 potentiated TRAIL-mediated apoptosis by lowering the levels of anti-apoptotic proteins and simultaneously stimulating the levels of DR5.…”
Section: Targeting Of Oncogenic Network In Trail Pathwaymentioning
confidence: 67%
“…CUDC-907 is an efficient dual-acting inhibitor of PI3K (phosphoinositide 3-kinase) and HDAC (histone deacetylase) (30). CUDC-907 stimulated DR5 expression, lowered the levels of anti-apoptotic proteins Bcl-2, Bcl-xL and XIAP.…”
Section: Targeting Of Oncogenic Network In Trail Pathwaymentioning
confidence: 99%